The Role of Artificial Intelligence in Primary School Education: A Literature Review on Robotics and Chatbots as Educational Partners - Abidin, Zainal; Kusumadewi, Rida Fironika (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
This study aims to examine the role of AI, particularly educational robotics and chatbots, as learning partners for elementary students through a systematic literature review approach. Data were collected from journal articles, conference proceedings, and research reports published between 2022 and 2025. The analysis integrates qualitative content analysis (coding, categorizing, and thematic synthesis), bibliometric mapping using VOSviewer, and citation analysis using Publish or Perish to identify research trends, dominant themes, and existing gaps. The findings indicate that educational robotics enhances students’ motivation, critical thinking, and collaboration through experiential and STEM-based learning, while AI-powered chatbots support personalized learning by providing instant feedback and fostering learner autonomy, particularly in language literacy and basic mathematics. However, the results reveal that AI is still predominantly positioned as a supporting instructional tool rather than a fully developed learning partner. Bibliometric and citation analyses further indicate a fragmentation between technological advancement and its pedagogical application in primary education, especially in relation to affective and socio-emotional aspects. The implementation of AI also faces several challenges, including limited infrastructure, high costs, and varying levels of digital literacy among teachers. This study concludes that optimizing AI as a learning partner requires stronger alignment between technology, pedagogy, and learner characteristics. The findings contribute to the development of pedagogically meaningful AI integration and provide recommendations for educators, technology developers, and policymakers.